Comparison of incidence/occurrence of cardiovascular events between ponatinib vs bosutinib among patients with at least one prior line of tyrosine kinase inhibitors in chronic myeloid leukemia in a community setting in the United States. (2021) - Levy, Moshe; Xie, Lin; Wang, Yuexi; Neumann, Frank; Srivastava, Shouryadeep; Naranjo, Daniel; Xu, Jing; Zhang, Qisu; Dalal, Mehul
Highlights: CV events were evaluated in CML patients treated with ponatinib or bosutinib. Other studies have demonstrated varying rates of toxicity and CV events among TKIs. Adult CML patients with prior TKIs were selected from the MarketScan® database. Ponatinib and bosutinib didn't have significant differences in CV event incidence. Abstract: Introduction: In this real-world study, the incidence of cardiovascular events (CV) including major adverse cardiac events (MACE), arterial occlusive events (AOE), and venous occlusive events (VOE) was evaluated in chronic myeloid leukemia (CML) patients treated with ponatinib or bosutinib in a US commercial database population. Materials and Methods: CML patients aged ≥18 years with use of 1 or 2 prior tyrosine kinase inhibitors prescribed bosutinib or ponatinib were selected from the IBM® MarketScan® Research database. Cox proportional hazard model analyses were conducted to examine any difference in CV event risk. Results: Ponatinib and bosutinib was associated with similar incidence and risk of CV events, including MACEs (HR: 1.02; 95% CI: 0.35, 3.01), AOEs (HR: 0.90; 95% CI: 0.43, 1.85) and VOEs (HR: 0.92; 95% CI: 0.44, 1.94). Conclusion: Treatment with ponatinib or bosutinib was not associated with significant differences in the incidence of CV events in CML patients.